Immunomodulatory Effects in Healthy Individuals Following a 4-Week Taoist Qigong Intervention: A Comparative Study. - Manzaneque-Vázquez, Juan Manuel; Vera-Fernández, Francisca María; Rodríguez-Peña, Francisco Miguel; Alonso, Antonio; Blanca-Mena, María José (International Scientific Information, 2023)
Qigong, an ancient health preservation technique forming part of Traditional Chinese Medicine, combines slow body movements, breathing, and meditation. While this meditative movement system has been reported to offer various physical and psychological benefits, studies on the Taoist school of qigong are sparse. This study, therefore, aimed to investigate the effects of Taoist qigong on white blood cells and other immune parameters in healthy individuals. MATERIAL AND METHODS Thirty-eight participants were recruited for the study, with 21 assigned to the experimental group and 17 to the control group. Participants in the experimental group engaged in a four-week Taoist qigong program. Blood samples for immune parameter quantification, including leukocyte count, neutrophil, eosinophil, basophil, lymphocyte, and large unstained cell (LUC) counts, as well as concentrations of IgG, IgA, IgM, C3, and C4, were collected one day before the experiment started and one day after it ended. RESULTS Post-program, the experimental group exhibited significantly lower total leukocyte counts, and reduced numbers of lymphocytes and LUCs. Additionally, a higher percentage of monocytes was noted in this group. CONCLUSIONS Taoist qigong practice induced a distinct immunomodulatory profile, characterized by decreased counts of several white blood cell parameters and increased percentages of certain agranulocytes. This outcome presents intriguing implications from a psychobiological perspective and highlights the need for further research into the immune effects of Taoist mind-body practice.
Keywords: Medicina china; Immunomodulation; Qigong; Mind-body therapies